Palinología de la Formación San Telmo (Carbonífero Superior) en la sierra San Antonio, provincia de Salta, Argentina (Ameghiniana, 2014)
New palynological information recovered from the middle part of the San Telmo Formation, upper part of the Mandiyutí Group, at the San Antonio range, Argentinean portion of the Tarija basin, is presented. Sixty five species of indigenous palynomorphs were identified, together with reworked specimens from the Upper Devonian and also Lower Carboniferous levels. The age of the indigenous assemblage is Late Carboniferous (~ Stephanian) and it can be correlated with a similar assemblage, from the outcrop of the Caraparí river at the Aguaragüe range. The age and correlation of the Mandiyutí Group is extensively discussed in order to reject a Early Carboniferous age suggested by some authors.